A chalcid wasp acts chiefly as a hyperparasitoid by mostly using small uncommon hosts. Issue 2 (27th December 2013) - Macedo, Margarete V.; Monteiro, Ricardo F.; da Fonseca, Adriana M.; Mayhew, Peter J.
Abstract Although ovipositing insects may predominantly use resources that lead to high offspring quality, exceptions to this rule have considerably aided understanding of oviposition decisions. We report the frequency of host species use by a solitary facultative hyperparasitoid, Brachymeria subrugosa Blanchard (Hymenoptera: Chalcididae). In our samples, the wasp attacks the large pupae of the moth Gonioterma indecora Zeller (Lepidoptera: Elachistidae), as well as the considerably smaller, and rarer, pupae of two of its other parasitoids. Consistent with conditional sex allocation models, the wasp produced mainly female offspring on the largest (moth) host, an unbiased sex ratio on the middle‐sized (parasitoid) host, and only males on the smallest (parasitoid) host. Adult offspring size was correlated with the size of the host attacked. These features strongly suggest that the two smaller, primary parasitoid, hosts produce lower‐quality offspring. Despite being more common, the proportion of hosts from which parasitoids emerged was lowest (14%) on the largest host species, and highest on the rarer middle‐sized (34%) and smallest (30%) hosts. This suggests that costs or constraints on attacking high‐quality primary hosts may be a selective force favouring the evolution of hyperparasitism.